Emotion Regulation in Borderline Personality Disorder: An Experimental Investigation of the Effects of Instructed Acceptance and Suppression. Issue 6 (November 2017) - Dixon-Gordon, Katherine L.; Turner, Brianna J.; Zachary Rosenthal, M.; Chapman, Alexander L.
Abstract: Difficulties with emotion regulation are central to borderline personality disorder (BPD). Recent research suggests that avoidance of emotions in general, and emotion suppression specifically, may be commonly used among those who meet criteria for the disorder. Contemporary behavioral interventions for BPD incorporate cognitive and behavioral skills to increase emotional experiencing and acceptance while decreasing behaviors that function to escape or avoid from emotions. Few studies, however, have experimentally examined the effects of instructed emotion suppression and acceptance in BPD. The present study examined the effects of instructed use of different emotion regulation strategies on emotions, psychophysiology, and behavior in BPD. Participants with BPD, major depressive disorder (MDD), and nonpsychiatric controls ( N = 193) were randomly assigned to either suppress or accept emotions during an audio recording of a social rejection scenario, and completed a behavioral measure of distress tolerance. BPD participants exhibited greater heart rate variability in the acceptance (vs. suppression) condition; this pattern was not evident within the other groups. These results suggest that deliberate use of acceptance-based emotion regulation strategies may have unique physiological effects among individuals with BPD. Highlights: We examined instructed suppression versus acceptance. Participants had borderline personality disorder (BPD), depression, or no disorder. BPD participants exhibited greater heart rate variability after acceptance.